Human polyomavirus (BK) infection and ureteric stenosis in renal allograft recipients. - Coleman, D V (1978)
Human polyomavirus (BK) was detected in two renal allograft recipients as a result of routine examination of Papanicolaou-stained smears of urinary sediment in the light microscope. Infection with this recently identified virus was confirmed by virus isolation and electron microscopy. The cytological, histological, and ultrastructural changes due to the virus are described, and virus excretion is correlated with the clinical progress of the patients and the pathological findings. The transplant ureters in both patients were found to be ulcerated and stenosed, and virus-infected cells were observed in the ureteric epithelium. We suggest that the administration of high-dose steroids in transplantation may permit active infection with human polyomavirus to occur in ureteric epithelium which has been damaged by ischaemia or inflammation.